Riboflavin detection by α-Fe2O3/MWCNT/AuNPs-based composite and a study of the interaction of riboflavin with DNA1. Issue 23 (13th March 2015) - Sumathi, C.; Muthukumaran, P.; Radhakrishnan, S.; Ravi, G.; Wilson, J.
<x xml:space="preserve">Abstract</x> The electrochemical behavior of riboflavin (RF) at a glassy carbon electrode modified with α-Fe2O3/MWCNT/AuNPs was investigated by cyclic voltammetry (CV) and square wave voltammetry (SWV).